The relation between holistic processing as measured by three composite tasks and face processing: A latent variable modeling approach - Ventura, Paulo (2022)
We investigated the relationship between holistic processing and face processing using a latent variables approach. Three versions of the composite paradigm were used to measure holistic processing: Vanderbilt Holistic Face Processing Test, a sequential composite matching task, and a simultaneous composite matching task. Three tasks were used to measure face perception and face memory abilities respectively. We had three pairs of tasks such that within each pair (of memory and perception task), the stimuli involved, the requirement for matching across viewpoints, etc., are the same, such that the only difference is whether perception or memory is taxed. There were no significant correlations between the different versions of the composite task. We discovered no evidence to support a distinction between face perception and face memory, suggesting the existence of a general face processing factor. Finally, there was no evidence that holistic processing (as captured by either of the three composite tasks) is predictive of better face processing per se, casting doubts on the role of holistic processing in differentiating different levels of efficiency in face processing.